Answer:
C is your answer!
Step-by-step explanation:
7 + 5 = 12 easy peazy!
![\frac{3}{7}*r + \frac{5}{8} *s](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B7%7D%2Ar%20%2B%20%5Cfrac%7B5%7D%7B8%7D%20%2As%20%20)
let us first plug the values of r and s here
r=14 and s=8
![\frac{3}{7}*14 + \frac{5}{8} *8](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B7%7D%2A14%20%2B%20%5Cfrac%7B5%7D%7B8%7D%20%2A8%20%20)
Now here we can cancel 14 and 7 as 7*2 =14 , also we can cancel 8 and 8 as 8*1 is 8, so our simplified new form is:
![\frac{3}{1}*2 + \frac{5}{1} *1](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%2A2%20%2B%20%5Cfrac%7B5%7D%7B1%7D%20%2A1%20%20)
Now we can multiply 3*2 and 5*1
3*2 =6
5*1=5
Next we add the two numbers
6+5 =11
So this is how we get the answer 11
Given:
Replace f(x) by f(x - h).
To find:
The effect on the graph of replacing f(x) by f(x - h).
Solution:
Horizontal shift is defined as:
If the graph f(x) shifts h units left, then f(x+h).
If the graph f(x) shifts h units right, then f(x-h).
Where, h is a constant that represents the horizontal shift.
In the given problem f(x) is replaced by f(x - h) and we need to find the effect on the graph.
Here, we have x-h in place of x.
Therefore, the graph of f(x) shifts h units right to get the graph of f(x-h).
(3/20)^3
27/8000
..............
Answer:
3 cm
Step-by-step explanation: